IMPLEMENTASI PEMBELAJARAN MENULIS KARANGAN EKSPOSISI - Edi Saputra (AXIOM : Jurnal Pendidikan dan Matematika, 2016)
Education is carried out and given to every citizen Indonesia to notleave any discrimination between formal, informal and non-formal. Thewrite language ability is absolutely necessary in today's modern life.Based on the fact turns writing skills have received less attention inschools especially those at the level of senior high school. The writtenis one of the four language skills to be learned by students. Theexposition essay used to convey the popular scientific descriptions orthe other scientific description that do not aim to influence readers.Before drawing up a bouquet of exposition course we need to preparethe data or facts needed to explain the problems discussed.